Bibliometric analysis of global research on PD-L1/PD-1 pathway and neurodegenerative diseases over the last two decades (2004–2023) - Wu, Jialin; Zhang, Chaojin; Cao, Qiang; Xuan, Wei; Huai, Xiaorong; Zhou, Jie; Tian, Jie (Frontiers in Aging Neuroscience, 2025)
BackgroundProgrammed death receptor 1 (PD-1), encoded by the PDCD1 gene, functions as a pivotal immunosuppressive molecule. Neurodegenerative diseases (NDDs) encompass a diverse array of neurological disorders that adversely impact the lives of millions of individuals globally. The current study discusses the impacts of PD-L1/PD-1 signaling on NDDs.MethodsA comprehensive online search was conducted using the Web of Science Core Collection database (WOSCC), with a limited time frame set from 2004 to 2023. Data were analyzed with CiteSpace, VOSviewer, and bibliometric package to explore trends in research output, key authors, institutions, journals, and thematic developments.ResultsThis study analyzed 366 publications within the field of PD-L1/PD-1 and NDDs. During 2004–2023, there’s an overall upward trajectory in the number of publications as the years progressed. The United States has a significant influence in this field, accounting for the highest number of publications. It also boasts the top two authors, six of the top 10 journals, and four of the top five institutions in terms of article count. Keyword burst analysis identified EAE, Parkinson’s disease, adaptive immunity, immune checkpoint blockade, and cerebrospinal fluid are research hotspots in recent years.ConclusionThis field has garnered increasing research attention, with the United States being the primary contributor. Recent studies have concentrated on the mechanisms through which PD-L1/PD-1 influences NDDs, and research into cerebrospinal fluid may persist as a focal point in the years to come. While the neuroprotective vs. neurodegenerative effects of PD-L1/PD-1 signaling remain controversial, this pathway represents a promising diagnostic and therapeutic target for NDDs.